Definition of the Ichthyurus davidi species group (Coleoptera: Cantharidae), with description of new species and additional faunistic records from China - Zhang, Wen-Wen; Liu, Hao-Yu; Yang, Xing-Ke; Yang, Yu-Xia (Zootaxa, 2026)
The Ichthyurus davidi species group is proposed based on the anatomical comparison. It comprises a total of nine species, including I. davidi Gestro, 1892, I. senensis Pic, 1926, I. laniger Gestro, 1891, I. platyurus Gestro, 1906, I. bisignatus Pic, 1926, I. maculicollis Gestro, 1888 (new record to China), I. luctuosus Gestro, 1891 (new record to China), I. vitalisi Gestro, 1918 (new record to China), and I. medogensis sp. nov. (China: Xizang). These species are illustrated with habitus and genital segments of both sexes, mesothoracic legs and aedeagus of the male, as well as internal genitalia of the female. A key for identification and a distribution map of this species group are provided.